Occupy religion : theology of the multitude - Rieger, Joerg (Religion in the modern world (Lanham, Md.), 2012)
Occupy Religion introduces readers to the growing role of religion in the Occupy Movement and asks provocative questions about how people of faith can work for social justice. From the temperance movement to the Civil Rights movement, churches have played key roles in important social movements, and Occupy Religion shows this role is no less critical today.